Loss of GGN leads to pre-implantation embryonic lethality and compromised male meiotic DNA double strand break repair in the mouse. - Duangporn Jamsai; Anne E O'Connor; Kathleen D Deboer; Brett J Clark; Stephanie J Smith; Catherine M Browne; Jonathan G Bensley; Julie A Merriman; Wai Shan Yuen; Peter Koopman; Keith T Jones; Moira K O'Bryan (PLoS ONE, 2013)
The integrity of male germ cell genome is critical for the correct progression of spermatogenesis, successful fertilization, and proper development of the offspring. Several DNA repair pathways exist in male germ cells. However, unlike somatic cells, key components of such pathways remain largely unidentified. Gametogenetin (GGN) is a testis-enriched protein that has been shown to bind to the DNA repair protein FANCL via yeast-two-hybrid assays. This finding and its testis-enriched expression pattern raise the possibility that GGN plays a role in DNA repair during spermatogenesis. Herein we demonstrated that the largest isoform GGN1 interacted with components of DNA repair machinery in the mouse testis. In addition to FANCL, GGN1 interacted with the critical component of the Fanconi Anemia (FA) pathway FANCD2 and a downstream component of the BRCA pathway, BRCC36. To define the physiological function of GGN, we generated a Ggn null mouse line. A complete loss of GGN resulted in embryonic lethality at the very earliest period of pre-implantation development, with no viable blastocysts observed. This finding was consistent with the observation that Ggn mRNA was also expressed in lower levels in the oocyte and pre-implantation embryos. Moreover, pachytene spermatocytes of the Ggn heterozygous knockout mice showed an increased incidence of unrepaired DNA double strand breaks (DSBs). Together, our results suggest that GGN plays a role in male meiotic DSB repair and is absolutely required for the survival of pre-implantation embryos.